(3TQM bUjOI GdHQOI ddHhUjQis - (3eMeO Hf SYjO Hf MeGO Hf YHO Gddg GdUfgGLj GdHhUjQj GdeUQj, TQa GdOjf, CHh YHO Gddg , (B696 (3g` s
(3ChdgG (B:s
(3hbdH eVWQe efg Ci eTJYd hGdGSJagGe ddJYLH GdEfcGQ Ci eG jfHZi ddeMH Cf jXf GfcJGe MHg Yf GdfGS ai MGd XghQg HGfSLGe LeYg s
(3BNQgG (B:s
(3aQCjJ GdfHi Udi Gddg Ydjg hSde aeSM HjOg GdeHGQcg Ydi aYhajJ ef hbJi hbGd aQCi adGf ai Gdfhe bO CTQa Ydi GdYei bGFdkG jbhd deG GLYd GdHQOg Ydi Yjfc Jab aYhai dhbJg s
(3fSNI KGfjIs
(3hHBNQgG UaMGJgG JYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B11s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B169 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1333s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs